A new speech cryptosystem using DNA encoding, genetic and RSA algorithms - F.Yousif, Sura (International Journal of Engineering and Technology, 2018)
A new system for speech signals encryption and decryption based on the combination of three different encryption techniques which are Deoxyribonucleic Acid (DNA) , Genetic and RSA algorithms is presented in this work. Initially, the one dimensional speech signal is divided to three equal blocks. Secondly, DCT is applied to each block to obtain coefficients of speech samples. Thirdly, each block of speech samples coefficients is encrypted using different encryption method, DNA encoding for the first block whereas Genetic algorithm and RSA algorithm are applied to the second and last blocks respectively. Finally, the three encrypted blocks are combined together to produce ciphered speech signal ready for transmission. The presented speech cryptosystem is implemented and its performance is assessed via different speech encryption and decryption quality criterions and for various speech signals. The results of experiments and comparison prove that the presented algorithm achieves good results for both encryption and decryption and it has the ability to withstand various cryptographic attacks effectively. Further, several kinds of analysis have been performed on the proposed scheme like SNR, PSNR, Correlation Coefficient, NPCR and UACI which are reach to -61.4085 dB, 6.0671 dB, 0.00031683, 99.96 % and 37.2940 % respectively. All these tests reveal that the presented cryptosystem is appropriate to be applied in communication systems for secure real time speech encryption and decryption applications.
Keywords: Speech Encryption and Decryption; DNA Coding; Genetic Algorithm; RSA Algorithm; Security Analysis.